Learning on the Move. Social Education Handbook for Students - Bazuń, Dorota - ed.; Kwiatkowski, Mariusz - ed. (Warszawa: Oficyna Naukowa)
Student`s Handbook is created as a collection of materials facilitating the study of social and humanities. What this textbook will differ from the classical one is to show how information can be grounded and assimilated in the course of moving activities.
Keywords: edukacja mobilna; socjologia i społeczeństwo; podręcznik akademicki